Strategi Pengembangan Sumber Daya Manusia Dalam Era Digital Pada E-Commerce Di Kota Pekanbaru - Ar Royan, Fadhil; Nazwa, Maharani; Anggraini Nurfadliah, Shella; Aprilia, Shiva; Fazira, Winni; Riofita, Hendra (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2024)
This research aims to analyse HR development strategies in e-commerce companies in Pekanbaru City. Descriptive qualitative method was used involving 10 subjects from 5 largest e-commerce companies in Pekanbaru City. The results show the main challenges are rapid technological changes and the need for digital skills. The strategies implemented include continuous training, digital talent recruitment, performance management system improvement, and technology adoption for HR management optimisation. A thorough evaluation was conducted to assess the effectiveness of the strategies in supporting digital transformation. This research provides an in-depth understanding of HR development in the e-commerce era.